2022
DOI: 10.1111/pim.12955
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal worms and bacteria: From association to intervention

Abstract: A plethora of studies, both experimental and epidemiological, have indicated the occurrence of associations between infections by gastrointestinal (GI) helminths and the composition and function of the host gut microbiota. Given the worldwide risk and spread of anthelmintic resistance, particularly for GI parasites of livestock, a better understanding of the mechanisms underpinning the relationships between GI helminths and the gut microbiome, and between the latter and host health, may assist the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…For each individual animal, the treatment was classified as efficient (1) or not efficient (0) if the FECRi was equal to or above 95% (FECRi95) or 99% (FECRi99). The explanatory variables study region, host species, age, sex, ivermectin dose and route of administration were analysed in small ruminants naturally infected with strongyle nematodes.…”
Section: Goatsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each individual animal, the treatment was classified as efficient (1) or not efficient (0) if the FECRi was equal to or above 95% (FECRi95) or 99% (FECRi99). The explanatory variables study region, host species, age, sex, ivermectin dose and route of administration were analysed in small ruminants naturally infected with strongyle nematodes.…”
Section: Goatsmentioning
confidence: 99%
“…Parasitic worms are an important public health and veterinary problem worldwide. In tropical regions, including Sudan, helminths, such as nematodes, are able to cause significant morbidity and mortality in their hosts [1, 2]. In livestock, gastrointestinal nematodes (GINs) are causing significant losses in production.…”
Section: Introductionmentioning
confidence: 99%
“…), inhibit bacterial toxins, increase mucus secretion, and induce mucosal immunity [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]. Although the relationship between probiotics and parasites has been investigated in various studies [ 144 , 148 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ], there are very few reports related to Blastocystis and probiotics.…”
Section: Blastocystis and Probioticsmentioning
confidence: 99%
“…In mammals, many studies have shown the association between GI helminth infections and both the composition and functionality of the host’s gut microbiota [ 3 5 ]. The gut microbiota is a complex and diverse community of microorganisms residing in the GI tract, including bacteria, viruses, fungi, and other microorganisms that coexist in a synergistic balance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While challenging, understanding how GI parasites and microbes influence each other could promote the development of novel microbiome-targeting approaches and other bacteria-based strategies for parasite control. For instance, the intervention of the gut microbial communities, e.g., via the administration of probiotics and prebiotics, and the use of bioengineered bacteria and nutritional supplements, has been postulated as an alternative strategy for parasite control and management [ 3 , 5 , 19 , 20 ]. Despite the importance of GI nematode parasitism in domestic ruminants, little is known about the nature and strength of the interactions among GI helminths and microbiota.…”
Section: Introductionmentioning
confidence: 99%